2021
DOI: 10.3390/ijerph18179117
|View full text |Cite
|
Sign up to set email alerts
|

Can Exercise Help Regulate Blood Pressure and Improve Functional Capacity of Older Women with Hypertension against the Deleterious Effects of Physical Inactivity?

Abstract: Background: Sedentarism and inactivity are risk factors for the development of hypertension. Thus, the prevention of the natural process of biological and physiological aging of older women through physical exercise results in higher benefits in preventing cardiovascular diseases and can be a key factor for its treatment. Multicomponent exercise (METP) is a training method that may help older women with hypertension by improving their quality of life and their response to treatment. Methods: Twenty-eight older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
2
8
0
1
Order By: Relevance
“…Sobrinho et al [ 20 ] showed only 14 weeks of an METP combined with flexibility training is enough to promote increases in the flexibility of inactive older women and improvements in blood pressure. The hemodynamic and lipid profiles improved after the METP and were in line with the results of studies ( Table 3 ) [ 17 , 18 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] that concluded that exercise helps older women regulate their blood pressure, triglycerides and total cholesterol, such as a study by Tofas et al [ 38 ] that reported significant improvements in SBP and DBP after 8 months of resistance training.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Sobrinho et al [ 20 ] showed only 14 weeks of an METP combined with flexibility training is enough to promote increases in the flexibility of inactive older women and improvements in blood pressure. The hemodynamic and lipid profiles improved after the METP and were in line with the results of studies ( Table 3 ) [ 17 , 18 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] that concluded that exercise helps older women regulate their blood pressure, triglycerides and total cholesterol, such as a study by Tofas et al [ 38 ] that reported significant improvements in SBP and DBP after 8 months of resistance training.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, it shows that some of the benefits of exercise are maintained after three and twelve months. This study complements the published work [ 18 ] with the objective of mapping the volunteers who drop out of research.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations